Phase segregation affects electron-phonon coupling in perovskite solar cell materials - YAVUZ, İLHAN (My University, 2023)
Phase segregation has been described as a significant factor that limits solar cell efficiency and long-term stability in mixed organic-inorganic halide perovskite materials. It is often microscopically linked to the electron-phonon coupling when the device is under operation. Through computational calculations, Migdal-Eliashberg theory and the Fröhlich large polaron model, we examined the control of phase segregation, in bulk I/Br and FA/Cs mixtures, over the electron-phonon coupling strength. We revealed that either A-site or X-site phase segregation destabilizes the material but reduces the electron-phonon coupling and increases the charge carrier mobility. Segregation promotes higher frequency vibrations and phonon instability is generally caused by [PbI6]4− octahedral torsions and liberations in FA+. Phonon dispersion has stronger control over the electron-phonon coupling than electronic bands. We expect that our theoretical findings will influence future discussions regarding the interplay of phase segregation and electron-phonon interactions in perovskite solar cells.
Keywords: Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; MATERIALS SCIENCE, MULTIDISCIPLINARY; Genel Kimya; Fizik Bilimleri; Malzeme Kimyası; General Chemistry; Physical Sciences; Materials Chemistry